Lamb weight gain and reproductive performance of post-partum ewes supplemented with palm kernel cake and sexual stimulated by a ram - Lorenzo Buenabad-Carrasco; Juan Sicairos-Díaz; Paulina Vázquez-Mendoza; Brooke Latack; Raymundo Rodríguez De Lara; Juan González Maldonado (Acta Scientiarum. Animal Sciences, 2023)
The objective of this study was to evaluate the effect of palm kernel cake and ram effect on reproductive activity of postpartum and lactating ewes. Twenty multiparous ewes, five to eleven days postpartum, were separated into four different treatments: control, control-ram, palm and palm-ram. Body weight, difference in body weight recorded between days 0 and 42 of the experiment, diameter of the largest follicle at day zero of the study, number of ewes bearing a corpus luteum and pregnancy rate were measured in ewes. Average daily weight gain was measured in lambs. There was no effect (p ≥ 0.05) of palm kernel supplementation, ram stimulation, or their interactions on the weights of ewes and lambs. A greater number of ewes with corpus luteum (p < 0.05) were observed in ewes stimulated by rams than those not stimulated. The number of pregnant ewes was not affected by ram effect or palm kernel supplementation (p ≥ 0.05). In conclusion, the use of the ram effect increases the incidence of corpus luteum in postpartum and lactating ewes. In addition, palm kernel cake in the diet does not affect body weight of postpartum ewes and lambs.